VO#045 Quotation for special-shaped planter bench rev.00 - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the submission of quotation for special-shaped planter bench according to engineer's instruction of BRACU new campus project.